2022
DOI: 10.1155/2022/5163886
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Cervical Cancer Treatment Outcomes: Ten Years of Experience with the Vaginal Assisted Radical Laparoscopic Hysterectomy VARLH

Abstract: Background. LACC trial demonstrated inferiority of laparoscopic approach for the treatment of early-stage cervical cancer. There are still limited data from retrospective trials regarding whether survival outcomes after laparoscopic radical hysterectomy are equivalent to those after open abdominal radical hysterectomy. In this study, we present results of combined vaginal radical laparoscopic hysterectomy in the treatment of early-stage cervical cancer. Methods. This retrospective study was carried out at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that laparoscopic surgery can reduce the incidence of complications [ 32 , 39 ]. Thus, surgeons who are highly proficient with open surgery can perform laparoscopic surgery to capitalize on the advantages of the latter, such as a smaller surgical wound, less bleeding, clear visual field, flexible operation, and quick postoperative recovery, thereby reducing the incidence of complications [ 40 , 41 ]. Robot-assisted laparoscopy offers the advantages of a high-definition three-dimensional field of view, multi-dimensional flexible Endowrist movements, and stable tremor-filtered operations over simple laparoscopic surgery, which can better reduce the incidence of complications, shorten postoperative recovery time, and improve patient quality of life [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that laparoscopic surgery can reduce the incidence of complications [ 32 , 39 ]. Thus, surgeons who are highly proficient with open surgery can perform laparoscopic surgery to capitalize on the advantages of the latter, such as a smaller surgical wound, less bleeding, clear visual field, flexible operation, and quick postoperative recovery, thereby reducing the incidence of complications [ 40 , 41 ]. Robot-assisted laparoscopy offers the advantages of a high-definition three-dimensional field of view, multi-dimensional flexible Endowrist movements, and stable tremor-filtered operations over simple laparoscopic surgery, which can better reduce the incidence of complications, shorten postoperative recovery time, and improve patient quality of life [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, national comprehensive cancer network (NCCN) cervical cancer guideline [3] changed open surgery to the standard surgical approach. Later, many studies thought that there was no difference in oncology outcome between laparotomy and laparoscopic surgery for some cervical cancer staging [4][5] . In the limitations of LACC research, it was mentioned that this research failed to further analyze the differences of oncology outcomes between the two surgical approaches possibly caused by pathological factors, and the conclusion could not be extended to the oncology outcomes of low-risk cervical cancer patients.…”
Section: Introductiona Multicenter Laparoscopic Cervical Cancer Surge...mentioning
confidence: 99%
“…L. A. Torres-de la Roche et al described a possible complication of uterine artery embolization and discussed the role of hysterectomy as a secondary intervention after treatment failure in uterus-sparing techniques [8]. While Q. Zhang et al described the impact of B7-H4 expression in precancerous lesions of the uterine cervix and the decision-making process regarding follow-up and conization in patients with CIN2 [9], R. Wojdat et al presented a retrospective analysis of their experience with vaginal assisted radical laparoscopic hysterectomy in patients with cervical cancer in the post-LACC trial era [10]. The role of hysterectomy in the management of obstetrical complications, especially in peripartum hemorrhage, has been reviewed by D. Tsolakidis et al [11].…”
mentioning
confidence: 99%